A Review of Fungal-Derived Natural Dyes: Chemical Diversity and Multifaceted Health Benefits - Budipramana, Krisyanti; Setiawan, Vendra; Ratih, Ratih; Budi Pramana, Yanatra (Jurnal Tumbuhan Obat Indonesia, 2024)
Various industrial sectors, from food and drug production to textiles, have widely used pigments or dyes as coloring agents. Generally, we can distinguish between two types of coloring agents: synthetic and natural. Currently, the use of synthetic colorings is a topic of debate due to their potential health risks, toxicity, and environmental pollution. This prompts a deeper exploration of natural resources as a more secure substitute for coloring agents. Plants, animals, microbes, and fungi can all provide natural coloring agents. Besides animals and microbes, some challenges in developing plants as major sources of natural coloring agents include variations in production or harvest times, strongly influenced by season, weather, and the intensity of sunlight. These factors influence not only the stability of the produced color but also its physicochemical properties, such as solubility and pH.  Moreover, overexploitation of plants has an impact on ecosystem imbalances and leads to extinction. Among natural resources, pigments or dyes from fungi have shown their potential to address these challenges. This review focuses on the potential of various microfungi that produce natural dyes, especially from Monascaceae, Trichocomaceae, and Nectriaceae, as well as the classification based on their chemical structure. Furthermore, we describe their diverse biological impacts as antioxidants, antibiotics, antidiabetics, anticancer agents, and anti-cholesterol agents, along with their health advantages.